Performance Evaluation of Bimetallic Piston - Hangargi , Sumeet (International Journal of Psychosocial Rehabilitation, 2020)
Bimetallic pistons are most generally utilized in diesel motor vehicles for weight decrease and improved execution with long life. Aluminum composite is strengthened with cast iron addition to understand the bimetallic pistons. The holding among aluminum and cast iron is accomplished through a protected procedure named the Al-Balance process. To guarantee better holding, the addition is dunked in the liquid aluminum shower, this plunging time assuming a fundamental job. The present investigation centers on shifting the plunging time from 90 s to 5 min to and the ideal plunging time. Accomplishing the close to net state of the bimetallic pistons without harming the holding between the aluminum and cast iron is the significant test. This examination additionally gets ideal cutting parameters in killing such pistons with cubic boron nitride as a solitary device to machine the metal. The bond trustworthiness subsequent to machining is basically identified with the extent of the cutting powers.